2017
DOI: 10.3390/cryst7090266
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin g-C3N4 Nanosheet-Modified BiOCl Hierarchical Flower-Like Plate Heterostructure with Enhanced Photostability and Photocatalytic Performance

Abstract: Abstract:A novel ultrathin g-C 3 N 4 nanosheet-modified BiOCl hierarchical flower-like plate heterostructure (abbreviated as BC/CN) was constructed via a thermal polymerization of urea precursor followed with hydrolysis route. The as-prepared samples were well characterized by various analytical techniques. The morphological observation showed that hierarchical flower-like BiOCl nanoplates were discretely anchored on the surface of ultra-thin C 3 N 4 nanosheets. The photocatalytic performance of the as-prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 61 publications
3
15
0
Order By: Relevance
“…Thus, the removals of PPCPs are deduced to follow the aromatic ring-opening pathways (Huang et al, 2016). This is in line with a report conducted by Jia and his colleagues [27]. These findings suggested that combining g-C3N4 and ZnO would improve electron and hole separation, resulting in one of the best photocatalytic efficiency candidates [28,29].…”
Section: Resultssupporting
confidence: 91%
“…Thus, the removals of PPCPs are deduced to follow the aromatic ring-opening pathways (Huang et al, 2016). This is in line with a report conducted by Jia and his colleagues [27]. These findings suggested that combining g-C3N4 and ZnO would improve electron and hole separation, resulting in one of the best photocatalytic efficiency candidates [28,29].…”
Section: Resultssupporting
confidence: 91%
“…BiOCl has a band gap energy of 3.4 eV and responds to UV irradiation. 3335 Recently, different structures of BiOCl have been reported such as spheres, plates, and flower-like structures. 3639 Wang et al reported the use of g-C 3 N 4 for water splitting under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the discovery of visible light response photocatalysts has greatly increased the utilization efficiency of sunlight [2]. In addition to modifying the traditional photocatalytic material TiO 2 to achieve visible light response [3], numerous efforts have been directed toward the development of efficient visible light responsive photocatalytic materials such as BFO, BiVO 4 (BVO), and g-C 3 N 4 [4][5][6][7]. BiVO 4 is a typical narrow band gap semiconductor oxide with excellent visible light catalytic performance and high photoelectric conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%